Resistant Starch Contents of Native and Heat-Moisture Treated Jackfruit Seed Starch - Ornanong S. Kittipongpatana; Nisit Kittipongpatana (The Scientific World Journal)
Native jackfruit seed starch (JFS) contains 30% w/w type II resistant starch (RS2) and can potentially be developed as a new commercial source of RS for food and pharmaceutical application. Heat-moisture treatment (HMT) was explored as a mean to increase RS content of native JFS. The effect of the conditions was tested at varied moisture contents (MC), temperatures, and times. Moisture levels of 20–25%, together with temperatures 80–110°C, generally resulted in increases of RS amount. The highest amount of RS (52.2%) was achieved under treatment conditions of 25% MC and 80°C, for 16 h (JF-25-80-16). FT-IR peak ratio at 1047/1022 cm−1 suggested increases in ordered structure in several HMT-JFS samples with increased RS. SEM showed no significant change in the granule appearance, except at high moisture/temperature treatment. XRD revealed no significant change in peaks intensities, suggesting the crystallinity within the granule was mostly retained. DSC showed increases in Tg and, in most cases, ΔT, as the MC was increased in the samples. Slight but significant decreases in ΔH were observed in samples with low RS, indicating that a combination of high moisture and temperature might cause partial gelatinization. HMT-JFS with higher RS exhibited less swelling, while the solubility remained mostly unchanged.